PEMANFAATAN KAWASAN KONSERVASI HUTAN MANGROVE SEBAGAI EKOWISATA DI KAMPOENG KEPITING - I Gusti Agung Ayu Pramita Indraswari; Ni Putu Budiadnyani; I G A N Alit Sumantri; Putu Pande R. Aprilyani Dewi (CV. ALIM'SPUBLISHING, 2023)
The role of mangrove ecosystems is to absorb waves and storm winds, protect the coast and prevent abrasion. The problem that is often faced is the large number of mangrove forests that have been damaged, both by natural factors and irresponsible human activities. Efforts that can be made to help preserve mangrove forests are to conserve mangrove forests by planting mangrove seeds in the area. Through mangrove forest conservation, it can help revitalize mangrove forests in the Kampoeng Kepiting area. Ecotourism is an alternative program that can be applied to improve the welfare of the local community. Utilization of mangrove forest areas as ecotourism is considered to be able to help the economy around the area. The existence of ecotourism in Kampoeng Kepiting can attract tourists, especially eco travelers to enjoy tourist attractions in the Kampoeng Kepiting area with a pleasant green natural atmosphere..